Repeated blood transfusions: Identification of a novel culprit of early graft failure in children. (1st March 2018) - Therrien, Judith; Guo, Kenneth; Guo, Liming; Liu, Aihua; Marelli, Ariane
Abstract: Background: The attrition of right ventricle to pulmonary artery (RV-PA) grafts has been attributed in part to the body's immunologic response. We hypothesized that antibodies developed through blood transfusion, directed against the grafts, may result in accelerated degeneration and the need for re-intervention. Methods: This is a population-based study of the province of Quebec. We included children born between January 1, 1987 to December 31, 2006 who were diagnosed with a cono-truncal anomaly and had an RV-PA graft. The patients were followed for transfusion exposure and RV-PA graft re-intervention. Time to re-intervention in those exposed versus non-exposed was analyzed using Cox regression. Analysis was done in two time periods, before and after the calendar year 2000, given the change in blood preparation in the province of Quebec. Results: There were 413 patients who met the inclusion criteria of a cono-truncal disorder. Of the whole study population, 69% received a blood transfusion. Cox regression analysis showed that among patients who had the initial graft performed (n = 181) before year 2000, having 2 or more blood transfusion was associated with an nearly tripled risk of a re-intervention comparing to no blood transfusion (hazard ratio of 2.88; 95% confidence interval 1.05–7.91). In patients who had the initial graft performed after year 2000 (n = 232), the associated risk increase was 7-fold (hazard ratio of 7.01; 95% confidence interval 3.06–16.02). Kaplan-Meier analyses confirmed the significant difference in the re-intervention free survival probabilities between those who received 2 or more blood product transfusion and those who did not as well: prior to year 2000 (67.9% vs. 88.0% at 5 years, p = 0.0201) as well as after year 2000 (39.7% vs. 82.8% at 5 years, p < 0.0001). Conclusion: In this population-based analysis, repeated blood product transfusion was associated with a significant increased risk of a need for RV-PA graft re-intervention. This data strongly suggest that repeated blood transfusion may adversely impact graft longevity.